2013
DOI: 10.3389/fnsys.2013.00022
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory activity, phase differences, and phase resetting in the inferior olivary nucleus

Abstract: The generation of temporal patterns is one of the most fascinating functions of the brain. Unlike the response to external stimuli temporal patterns are generated within the system and recalled for a specific use. To generate temporal patterns one needs a timing machine, a “master clock” that determines the temporal framework within which temporal patterns can be generated and implemented. Here we present the concept that in this putative “master clock” phase and frequency interact to generate temporal pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 35 publications
8
21
0
Order By: Relevance
“…6A-B). Our network model confirms that gap junctional coupling can broaden the distribution of STO frequencies and that even non-oscillating cells may, when coupled, collectively act as oscillators (S6 Fig.) (67). Adding contextual input to the model network can lead to more spontaneous spiking in between two sensory stimuli.…”
Section: Resultssupporting
confidence: 73%
“…6A-B). Our network model confirms that gap junctional coupling can broaden the distribution of STO frequencies and that even non-oscillating cells may, when coupled, collectively act as oscillators (S6 Fig.) (67). Adding contextual input to the model network can lead to more spontaneous spiking in between two sensory stimuli.…”
Section: Resultssupporting
confidence: 73%
“…Subtheshold theta frequency oscillations in inferior olivary neurons may serve as a master clock for cerebellar generation of temporal patterns. In order to achieve precision greater than a theta period, it was recently suggested that the coupling between olivary neurons allows them to break into phase-locked clusters able to keep time at a higher resolution [60]. Phase-resetting theory constrains the tendency of networks to break up into clusters [31].…”
Section: Cerebellar Timing Mechanismsmentioning
confidence: 99%
“…On the part of the filtered neurograms corresponding to buccal activity only, we perform time-frequency transform with complex Morlet wavelets (CWT) that is adapted to non-stationary signals (Akay, 2005 . With adapted signal-processing tools, we evidenced, for the first time in amphibians, the presence of fast oscillations in the [20][21][22][23][24][25][26][27][28][29][30] Hz frequency band in the buccal bursts, probably resulting from phase locked motoneuron activities, which are reminiscent of some of the fast oscillations described in several species of mammals (Funk and Parkis, 2002;Rogers, 2006, 2007). Regarding the effects of hypercapnia (acidosis at pH=7.4) on the gill/buccal activity, our results show that there is no change of the fast oscillations in the premetamorphic tadpole, but significant changes in postmetamorphic ones.…”
Section: Introductionmentioning
confidence: 93%
“…In contrast with the premetamorphic tadpoles spectra, the amplitude of the first peak is systematically smaller in hypercapnia than in normocapnia, while there is an increase in the high frequency band. The statistical tests performed on the CWT spectral energies in the low frequency (1-10 Hz) and in the high frequency band (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) give the following results. For the effect of metamorphosis, the relative energy in the low frequency band is significantly higher for the postmetamorphic tadpoles at both pH: at pH=7.8, +0.33 (p=0.008) and at pH=7.4, +0.09 (p=0.029), while in the high frequency band it is significantly lower: at pH=7.8, -0.12 (p=0.008) and at pH=7.4, -0.04 (p=0.001).…”
Section: Cwt Maps and Spectra Of Buccal Activitymentioning
confidence: 99%
See 1 more Smart Citation